Sistema informático para la unidad de seguridad y salud ocupacional de la Espam MFL. - Barreiro Cedeño, Byron Jacinto (2015)
The development of the software application for the occupational safety and health department in the ESPAM MFL, it manages the processes that run on this unit, to the authors of the thesis was an arduous task, to give effect to the research and develop of the project, the same it was applied to the occupational safety and health unit of the ESPAM MFL, located in the Polytechnic Campus, from Lemon site, in Calceta City, parish and cantonal head of Bolivar, province of Manabí, 3 km. away from the city, it began with the capture of the requirements and development of the database, to thereby continue developing the contents of the computer application, then it was programmed each of the features, to do that, it was used the themes that are detailed in the framework of this report. With the MIDAS methodology and each, one of the technical tools, resources and materials made possible the realization of the computer system. Knowing that it is a vital necessity to include to the society our proposal, for doing this, it is required the learning and researching process to enhance knowledge in addition it is known that the theory is useless if it is not combined with practice.